Kemajemukan, Hipotesis Kebudayaan Dominan dan Kesukubangsaan - Parsudi Suparlan (Antropologi Indonesia, 1999)
On the basis of Bruner's concept of a dominant culture, the author analyzes the case of Bandung, Sambas, and Ambon. By comparing the three cases, the author reveals the differences in adaptation strategies among the Javanese in Bandung, the Maduranese in Sambas, and the BBM (Buton, Bugis, Makassar) in Ambon...[...] The author argues that the dominant culture in a specific setting, with its rules and norms, should be followed by the migrants and outsiders. However, the challenges to the dominant culture can be diverse in different societies and setting. The cases in Sambas and Ambon reveal that there is a problem in the challenge toward the dominant culture in those societies.